Estimating the bias in meta analysis estimates for continuous data with non-random missing study variance - Nik Idris, Nik Ruzni (Universiti Teknologi Malaysia, 2011)
This paper examines, analytically, the biases introduced in the meta analysis estimates when the study-level variances are missing with non-random missing mechanism (MNAR). Two common approaches in handling this problem is considered, namely, the missing variances are imputed, and the studies with missing study variances are omitted from the analysis. The results suggest the variance will be underestimated if the magnitude of the study-variances that are missing are mostly larger implying false impression of precision. On the other hand, if the missing variances are mostly smaller, the variance of the e®ect size will be overestimated.